Tokenização da propriedade imóvel no Brasil: realidade ou ficção? - Burtet, Tiago Machado (Universidade do Vale do Rio dos Sinos, 2024)
What were once predictions of the impact of technology in a distant future is now becoming a reality. In the age of artificial intelligence (ChatGPT, Microsoft 365 Copilot, Bard, etc.), the market dynamics are producing transformations and introducing innovations that need to be examined in the light of the Law. The tokenization of real estate fits into this techno-legal context and needs to be analyzed in the light of Legal Science in order to understand whether it is a viable activity or not, considering the current rules regarding the acquisition of real property rights. Therefore, it will be necessary to understand how the real estate property protection system in Brazil is structured: the Real Estate Registry. From then on, concepts related to tokenization and some ways of working with this new tool will be known. Finally, it will be analyzed whether it is possible to establish a true and secure connection between these new activities carried out in the digital environment with everything that can be achieved in the factual realm, in a valid and effective manner for the established legal framework. In this context, it will be possible to ascertain that in Brazil, a business is already being offered that aims to be characterized as a possible form of real estate tokenization, starting in Porto Alegre, through the company Netspaces Propriedades Digitais Ltda, which will be the subject of this investigation. This business intends to establish a new system in the digital environment, via Blockchain, aiming at the negotiation of crypto-assets, but in some way related to the Real Estate Registry. This is a different type of business from others also offered as real estate tokenization, however, without any connection to the established protection system. Thus, this dissertation aims to analyze the entire context involving the acquisition of real estate property in Brazil and determine whether the business model developed by the aforementioned company constitutes a real possibility of real estate tokenization that allows for improvements and advancement, or if it is a fiction. The methodology employed will be through the application of analytical methods (understanding the relevant legal framework) and empirical methods (comprehending the business idea devised by the company and its attempt to connect with the established system) regarding how each one (Real Estate Registry and business developed by the company) is structured. In addition to theoretical knowledge of what has already been researched on the subject up to the present moment, hoping to enable a critical evaluation at the end, both to recommend the maintenance of what is already known to be positive, as well as to foster new reflections and discussions on what can be improved in the aforementioned business.
Keywords: Tokenização; Registro; Propriedade; Imóvel; Brasil; Tokenization; Registry; Property; Immobile; Brazil; ACCNPQ::Ciências Sociais Aplicadas::Direito